THE POSITION OF WAKAF IN ISLAMIC LAW AND ITS IMPLEMENTATION IN INDONESIA - Sofia Fahrany; Siti Nur Intihani (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Waqf is the legal action of the Wakif (the person who gives the Waqf) to separate and/or hand over part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. Waqf is a sacred and noble legal act and as shodaqoh jariyah, as long as the items donated can be used by people who need them, the rewards will continue to flow even if the Wakif has died. The problems studied are: a) how to regulate Waqf according to Islamic law; b) how is the implementation of Waqf in Indonesia; c) how to resolve Waqf disputes in Indonesia. In this research, the author uses a normative juridical approach method. In normative legal research, secondary data will be examined which includes primary, secondary and tertiary legal materials, namely statutory regulations, Religious Court Decisions and Books and Journals. The research results illustrate that Waqf has been prescribed and has been implemented by Muslims since the time of the Prophet Muhammad SAW, the order for Waqf is contained in the Koran (QS Al-Baqarah verses 261 and 267, QS Al Maidah verse 2, QS Ali Imron verse 92, QS. Al -Hajj verse 77). The implementation of Waqf in Indonesia is regulated in Law Number 41 of 2004 concerning Waqf, its Implementing Regulations and the Compilation of Islamic Law. The pillars of Waqf include: 1) Wakif (person who is waqf), 2) Mauquf bih (Wakf assets), 3) Mauquf 'alaih (purpose of Waqf), 4) Shighat (statement or Pledge of Waqif as a will to donate part of his property) , 5) Nadzir (waqf manager) and 6) Waqf term. Resolving waqf disputes is achieved through deliberation to reach consensus. If resolution through deliberation is not successful, the dispute can be resolved through mediation, arbitration or the Religious Courts. Several cases regarding waqf have been examined and decided by the Religious Courts in Indonesia.